1982
DOI: 10.1530/jrf.0.0640019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive immunization against LH-RH on gonadotrophin secretion in the ferret

Abstract: Administration of ovine antiserum containing antibodies against synthetic LH-RH to spayed female ferrets caused an immediate fall in plasma LH concentration and by 2 h after injection circulating levels had declined by 70--80%. A further decline of 50% was observed on Day 2, but by Day 4 a return to normal levels had begun and control values were regained on Day 6. In contrast, the fall in plasma FSH concentration was delayed, with a significant reduction being first observed on Day 2 and minimal values occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the male rat, serum FSH values did decline 24 h after LH-RH antibody administration, but the fall was slower and less pronounced than for LH (Fraser, Sharpe, Lincoln & Harmer, 1982). Also, in the ovariectomized rat, rhesus monkey and ferret treated with LH-RH antibodies, FSH concentrations decline more slowly than do those of LH (Koch et ai, 1973;McCormack, Plant, Hess & Knobil, 1977;Gledhill, Fraser & Donovan, 1982 (Lincoln, 1979). In the present study we consider the most important influence on the pattern of FSH observed to be the changes in the levels of ovarian factors which feedback on the pituitary gonadotrophs.…”
Section: Discussionmentioning
confidence: 68%
“…In the male rat, serum FSH values did decline 24 h after LH-RH antibody administration, but the fall was slower and less pronounced than for LH (Fraser, Sharpe, Lincoln & Harmer, 1982). Also, in the ovariectomized rat, rhesus monkey and ferret treated with LH-RH antibodies, FSH concentrations decline more slowly than do those of LH (Koch et ai, 1973;McCormack, Plant, Hess & Knobil, 1977;Gledhill, Fraser & Donovan, 1982 (Lincoln, 1979). In the present study we consider the most important influence on the pattern of FSH observed to be the changes in the levels of ovarian factors which feedback on the pituitary gonadotrophs.…”
Section: Discussionmentioning
confidence: 68%
“…The decrement in plasma LH induced by a single shot of anti-LH-RH delivered to gonadectomized animals is typi cally never so great as to bring plasma LH down to the lev els found in intact animals [18,24,28]. The abolition of LH pulses by anti-LH-RH in the present study left plasma LH levels at 80-120 ng/ml, a level some 4-to 5-fold greater than that abserved in intact male rats, using the same radio immunoassay system [10].…”
Section: Discussionmentioning
confidence: 98%
“…The duration of LH suppression following a single infusion of anti-LH-RH is at least 3 h. Other experimenters employing a single injection of LH-RH antibodies report a suppression of LH lasting at least 24 h (female rat [24]), 2 days (ram [27]), 3 days (female ferret [18]), 7 days (male rat [14]), or 10 days (female rhesus monkey [28]). …”
Section: Discussionmentioning
confidence: 99%